Winkle the extraordinary life of Britain's greatest pilot - Beaver, Paul 1953- (Penguin Books, 2024)
The extraordinary life story of Captain Eric 'Winkle' Brown - aviator, record-breaker, and Britain's greatest pilot
Originally published: UK: Michael Joseph, 2023
Keywords: Brown, Eric Melrose; Air pilots, Military / Great Britain / Biography; Test pilots / Great Britain / Biography; Pilotes d'aéronef militaires / Grande-Bretagne / Biographies; Pilotes d'essai / Grande-Bretagne / Biographies; Biography